2021
DOI: 10.1021/acs.analchem.1c02906
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane-Based Face Mask as a Sampling Device for Environmental Tobacco Smoke

Abstract: Environmental tobacco smoke (ETS), also known as secondhand smoking, contains human carcinogens associated with the development of many human diseases, including stroke, heart disease, leukemia, and lung cancer. Due to these adverse health effects, a sensitive and selective method is crucial for assessing the health impacts of ETS. While current methods to evaluate ETS exposure are either invasive or nonspecific and insensitive, in this study, we assessed the use of polyurethane foam face masks as a sampling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Previous studies demonstrated that PP- and PUF-based face masks can efficiently block human exposure to airborne PAHs and tobacco-specific nicotine and have high filtration efficiency for particle-associated aerosols. ,, To develop face masks as a user-friendly air sampling device for assessing human exposure to multiple classes of VOCs and SVOCs, we initiated the study by testing the background levels of the target analytes in PUF-, PP-, and AC-based masks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that PP- and PUF-based face masks can efficiently block human exposure to airborne PAHs and tobacco-specific nicotine and have high filtration efficiency for particle-associated aerosols. ,, To develop face masks as a user-friendly air sampling device for assessing human exposure to multiple classes of VOCs and SVOCs, we initiated the study by testing the background levels of the target analytes in PUF-, PP-, and AC-based masks.…”
Section: Resultsmentioning
confidence: 99%
“…A total of six different brands of masks made of PUF (PUF 1 and PUF 2), polypropylene (PP, bacterial filtration efficiency ≥ 99%, PP 1 and PP 2), and activated carbon (AC, AC 1 and AC 2) were purchased from local pharmacies in Hong Kong. PP and AC masks were baked at 70 °C for 3 h prior to use and PUF masks were precleaned by soaking in IPA, ethanol, and water sequentially, and dried by baking at 100 °C before use, as described previously. , The precleaned PUF masks were used for sampling within 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…[ 101 ] with permission; e) facemask expose to tobacco smoke, reproduced from Ref. [ 102 ] with permission; f) paper strip outside in facemask to expose ambient air, reproduced from Ref. [ 77 ] with permission.…”
Section: Facemask Sampling Of Human Inhalable Environmental Exposuresmentioning
confidence: 99%
“…Mogridge et al [ 100 ] further assessed the comparability of facemask-based air sampler ( Figure 5 d) with the traditional inward leakage measurement technique. Facemask was applied as a personal dosimeter for quantifying environmental exposure to airborne PAHs ( Figure 5 e) and tobacco smoke ( Figure 5 f) in the Chan research group [ 101 , 102 ]. These studies showed that facemask could be a simple, convenient, and inexpensive sampler to collect inhalable air pollutants in the air compared with traditional filter/sorbent-based approaches, which usually require a sampling pump to continuously introduce the airflow.…”
Section: Facemask Sampling Of Human Inhalable Environmental Exposuresmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) and nicotine and nitrosamines from tobacco smoke have been directly sampled using a mask to represent their concentration in the air environment. 127,128 Yuan et al inserted a solid phase microextraction (SPME) fiber into a KN95 mask to collect substances from exhaled breath aerosol and analyzed its chemical composition. 129 Cai et al fixed paper strips on the surfaces of inner and outer layers of a KN95 mask to separately monitor substances in the exhaled aerosol and inhaled air.…”
Section: Measures To Maximize the Utilization And Minimize The Risks ...mentioning
confidence: 99%